Optimization of the Shortest Route Using the Djikstra Algorithm to the Nearest Covid-19 Referral Hospital for Communities Exposed to the District of Medan Baru - Yan Batara Putra Siringoringo; Asima Manurung; Enita Dewi Br Tarigan (Information Technology and Science (ITScience), 2025)
Abstract: Finding the shortest route is a problem to find a path that connects two nodes with the least amount of weight. Many methods are used in finding the shortest route. One of the methods used is Dijkstra's algorithm. Dijkstra's algorithm is an excellent algorithm used in determining the shortest route from a startingpoint toan end point (destination). In this study, the determination of the shortest route from each kelurahan in the Medan Baru District to the nearest Covid-19 referral hospital can be searched maximally using the Dijkstra algorithm with the distance taken through the google maps application. However, there are some limitations that are limitations in this study. The drawbacks are traffic jams, traffic lights, one-way streets. This cannot be ignored on routes in urban areas. In the future, researchers will look for optimization of determining the shortest route by including some of the problem constraints that occur. The Dijsktra algorithm is an application that must be modernized for more complex constraints.